The promise and limits of engaging international students through living-learning communities in U.S. research universities (Comparative & International Education Series, 2021)
This chapter explores the possibilities and limitations of using Living-Learning Communities (LLCs) to engage international students in U.S. research universities. LLCs are considered a high-impact practice by the Association of American Colleges and Universities (AAC&U), but research on their specific impact on the engagement of international students remains limited. Nevertheless, global or international “houses” or communities are nearly ubiquitous in American research universities. This chapter traces variations on this practice across institutional types, identifies promising practices, and explores limitations for implementing this approach. An LLC within a research university in the Northeast is presented as an instrumental case study to empirically anchor the theoretical discussion presented in the chapter. Class observations were conducted over the course of one year and semi-structured interviews took place with 14 international students. The chapter concludes with specific recommendations for the successful implementation of this practice.